//Fluxspace: temporary acts as social catalysts in Kansas City - Wagner, Benjamin N. (Kansas State University, 2013)
Kansas City is in the midst of an urban renaissance, with a construction boom within the downtown core in excess of $4.5 billion over the past several years (CVA 2012). In 2010, Kansas City’s Greater Downtown Area Plan (GDAP) was implemented to guide the future transformation and development of the city. Despite its long-term vision and specific goals, including activating the public realm and fostering a strong urban community (City Planning et al. 2010), the GDAP fails to address opportunities for short-term strategies for interim ‘place-making.’ Yet, temporary gatherings are critical to fostering and sustaining a sense of ‘place.’ Kansas City currently has an emerging, vibrant urban culture, but it lacks amenities and spaces to support and celebrate spontaneous social activity. To address this issue, this project proposes a series of prototypical fluxspaces – small, temporary interventions activated by the presence of food trucks - throughout Kansas City’s downtown area. These new temporary acts exploit the potential of underutilized urban surfaces in the short term while re-invigorating social activity and celebrating an emerging urban culture in the long term. Sites are linked to existing mobile food vending hot spots and interventions are timed in conjunction with major Kansas City events and festivals; this grounds the proposed system in Kansas City’s population of temporary users. A detailed schedule ensures that Kansas City’s fluxspaces feature a dynamic, rotating population of food trucks, while fluctuating amenities promote diverse, exciting, and attractive temporary places. Kansas City’s new fluxspaces accommodate spontaneous social gatherings and celebrate their vital importance in fostering a vibrant urban environment. //fluxspace activates Kansas City’s latent urban surfaces, filling the gap between Kansas City’s immediate need for places of temporary gathering and the long-term goals inherent in the vision for Kansas City’s future.
Flux space
Keywords: Kansas City; Place-making; Temporary; Spontaneous; Food trucks; Underutilized; Landscape Architecture (0390)